ANALISIS PENGARUH LIKUIDITAS , UKURAN PERUSAHAAN (FIRMSIZE), DAN DEVIDEN PAYOUT RATIO (DPR) TERHADAP PRICE EARNING RATIO PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BEI - Dwi Artati; Bibit Puji L (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2019)
The purpose of this study was to investigate Current Ratio,Firm Size,and Deviden payout ratio, and to Price Earnings Ratio. This study focused on property and real estatelisted in Bursa Efek Indonesia for period 2012-2016.The method of data collecting was done by conducting documentation secondary data using the financial statement of property and real estatecompanies at BEI and other seconder data. The method of analyses which used weremultiple linier regression analyses. The instrument statistik which used was SPSS. The result of this study showed that Current Ratio (CR) has unsignificant (0,867). Firm Size hasunsignificant (0,178) effect to Price Earnings Ratio. Deviden payout ratiohas significant (0,000) effect to Price Earnings Ratio. The simultaneous testing showed that Current Ratio, Firm Size,and Deviden payout ratiowere influenced to Price Earnings Ratio with count F value (5,64) and significant (0,002). The adjusted R2 was 0169, that showed the influence of Current Ratio, Firm Size, and Deviden payout ratioto Price Earnings Ratio value at 16,9 %